Developing a Prototype of a Self-Regulated Learning-Based Learning Model for English Language Learning for Junior High School: Introduction, The Objectives, Method, Result and Discussion, Conclusion
This study aims to develop a prototype learning model based on self-regulated learning for students who study English at Junior High School, and find effective strategies to support teachers in adopting and adapting self-regulated learning-based learning in their English classes. The era of globalization requires mastery of English language to access global information, communicate among countries, and increase competitiveness. The 2045 Golden Indonesia Vision [5